Higher order chromatin organization in cancer - Reddy, Karen L. (2012)
In spite of our increased understanding of how genomes are dysregulated in cancer and a plethora of molecular diagnostic tools, the front line and ‘gold standard’ detection of cancer remains the pathologist’s detection of gross changes in cellular and tissue structure, most strikingly nuclear dis-organization. In fact, for over 140 years it has been noted that nuclear morphology is often disrupted in cancer. Even today, nuclear morphology measures include nuclear size, shape, DNA content (ploidy) and ‘chromatin organization’. Given the importance of nuclear shape to diagnoses of cancer phenotypes, it is surprising and frustrating that we currently lack a detailed understanding to explain these changes and how they might arise and relate to molecular events in the cell. It is an implicit hypothesis that perturbation of chromatin and epigenetic signatures may lead to alterations in nuclear structure (or vice versa) and that these perturbations lie at the heart of cancer genesis. In this review, we attempt to synthesize research leading to our current understanding on how chromatin interactions at the nuclear lamina, epigenetic modulation and gene regulation may intersect in cancer and offer a perspective on critical experiments that would help clarify how nuclear architecture may contribute to the cancerous phenotype. We also discuss the historical understanding of nuclear structure in normal cells and as a diagnostic in cancer.